Beyond Hepatocellular Carcinoma and Colorectal Metastasis: The Expanding Applications of Radioembolization - Zurkiya, Omar; Ganguli, Suvranu (Frontiers in Oncology, 2014)
As a relatively safe outpatient procedure, radioembolization can potentially be used to treat any type of tumor within the liver, primary or metastatic. The safety and effectiveness of radioembolization in the treatment of hepatocellular carcinoma (HCC) and metastatic colorectal cancer (mCRC) has led many groups to explore its application in other malignancies. Moreover, other organs, such as the lungs and kidneys, have been explored as targets for therapy. Although the most data for radioembolization is related to HCC and mCRC, there is increasing experience and data regarding metastatic disease to the liver for other primary tumors. We review the current state of liver-directed therapy with radioembolization outside of HCC and mCRC, including metastatic neuroendocrine, breast and melanoma, as well as limited experiences with other primary malignancies. Applications of radioembolization related to these other cancers and new trends and future directions will be discussed. With increasing use and availability of radioembolization, it promises to serve an expanding role in the repertoire of tools available for treating and managing oncologic disease.